The sequences { a n } , { b n } satisfy n → ∞ lim a n = 3 , n → ∞ lim b n = 5 . Find
n → ∞ lim n 1 k = 1 ∑ n a k b n − k
Prove it for any { a n } , { b n } generally.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Just because lim n → ∞ f ( n ) = 0 doesn't meant that ∑ k = 1 ∞ f ( k ) < ∞ . E.g. the harmonic series.
You're right. I seemed to have overlooked the harmonic series and sequences like it. However, unless I am misunderstanding something, the series b n = n 1 + 5 seems to invalidate the given statement "Prove it for any a n , b n generally" since b n − k is undefined for k = n . Granted, b n = n + 1 1 + 5 is valid and my solution fails to correctly explain why the limit of the sum is 15.
Here's a "fakesolve" solution:
Let { a n } = 3 for all n , and { b n } = 5 for all n . Then it is obvious that a k b n − k is equal to a constant, 1 5 . Because the summation means we are adding 1 5 n times, the limit evaluates to n → ∞ lim n 1 5 n , which simplifies to 1 5 .
Obviously, the question asks to prove it for general { a n } and { b n } , but this is a start.
I'm not the only one used this approach
Problem Loading...
Note Loading...
Set Loading...
The sequences a n and b n can be represented as f ( n ) + 3 and g ( n ) + 5 respectively where f ( n ) and g ( n ) may or may not be equal to each other and lim n → ∞ f ( n ) = 0 and lim n → ∞ g ( n ) = 0 . If we substitute these formulas for a n and b n − k we get:
n → ∞ lim n 1 k = 1 ∑ n ( f ( k ) + 3 ) ( g ( n − k ) + 5 )
Which if we expand gives us
n → ∞ lim n 1 k = 1 ∑ n ( f ( k ) g ( n − k ) + 3 g ( n − k ) + 5 f ( k ) + 1 5 )
The 1 5 can be easily factored out to become 1 5 n . As for the rest of the terms, ∑ k = 1 ∞ f ( k ) = constant since lim n → ∞ f ( n ) = 0 and ∑ k = 1 ∞ g ( n − k ) = constant since lim n → ∞ g ( n ) = 0 and ∑ k = 1 n g ( n − k ) = ∑ k = 0 n − 1 g ( k ) . In the case of, if we take n to infinity, ∑ k = 1 n f ( k ) g ( n − k ) = f ( 1 ) g ( n − 1 ) + f ( 2 ) g ( n − 2 ) + . . . + f ( n − 1 ) g ( 1 ) + f ( n ) g ( 0 ) we always have one "large" number countered by a "really small number" (for instance, f ( 1 ) is relatively large compared to g ( n − 1 ) which is near zero). As such, the sum should be a constant.
Therefore, we have:
k = 1 ∑ n ( f ( k ) g ( n − k ) + 3 g ( n − k ) + 5 f ( k ) ) = constant
meaning that the limit simplifies to
n → ∞ lim n 1 k = 1 ∑ n ( constant + 1 5 n ) = 0 + 1 5 = 1 5